2020
DOI: 10.1002/essoar.10505582.1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deglacial ice sheet instabilities induced by proglacial lakes

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 45 publications
2
10
0
Order By: Relevance
“…The presence/absence of a lake, water level, water temperature and any sudden changes in those lake properties could affect glacier dynamics within lake catchments. Importantly, the alpine literature (e.g., see citations within Carrivick et al., 2020) and numerical models (Hinck et al., 2020; Quiquet et al., 2021; Sutherland et al., 2020) show that these effects could persist many kilometres up‐ice from those lakes, especially where glaciers sit on retrograde bed slopes (i.e., overdeepened valleys/basins).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence/absence of a lake, water level, water temperature and any sudden changes in those lake properties could affect glacier dynamics within lake catchments. Importantly, the alpine literature (e.g., see citations within Carrivick et al., 2020) and numerical models (Hinck et al., 2020; Quiquet et al., 2021; Sutherland et al., 2020) show that these effects could persist many kilometres up‐ice from those lakes, especially where glaciers sit on retrograde bed slopes (i.e., overdeepened valleys/basins).…”
Section: Discussionmentioning
confidence: 99%
“…Increases in lake‐terminating ice‐marginal environments will also increase potential for more rapid ice sheet mass loss through both iceberg calving and lake‐enhanced melt of the ice margin itself (e.g., Schomacker, 2010). Ice‐marginal lakes have also been invoked as a potential catalyst for inducing exceptionally rapid ice margin retreat (Carrivick et al., 2020; Hinck et al., 2020; Quiquet et al., 2021; Sutherland et al., 2020), especially where there is progressive ice‐margin retreat down a retrograde bed slope (Truffer and Motyka, 2016) in a manner highlighted for marine termini by Crawford et al. (2021).…”
Section: Introductionmentioning
confidence: 99%
“…Including proglacial lakes explicitly or as boundary conditions in ice‐sheet models enhances ice loss through localized mechanical instabilities (Hinck et al., 2022; Quiquet et al., 2021; Sutherland et al., 2020), which Quiquet et al. (2021) termed “proglacial lake ice sheet instability” (PLISI). Modeling the Laurentide ice sheet, Quiquet et al.…”
Section: Introductionmentioning
confidence: 99%
“…Modeling the Laurentide ice sheet, Quiquet et al. (2021) found that ice margins retreat faster when abutting proglacial lakes especially if the bedrock dips toward the ice interior (often due to ice loading). This finding suggests that proglacial lakes influence ice‐sheet stability.…”
Section: Introductionmentioning
confidence: 99%
“…In Manitoba, deglacial ice margins were in contact with Lake Agassiz, which likely affected the stability of the ice (Quiquet et al . 2021; Hinck et al . in press).…”
mentioning
confidence: 99%